Comparative Study of Municipal Solid Waste Using by Lampito Mauritii and Eudrilus Eugeniae Earthworms Enhance for Microbial Enzyme Activity: Comparative Study of Municipal Solid Waste Using by Lampito Mauritii and Eudrilus Eugeniae Earthworms Enhance for Microbial Enzyme Activity - Ananthakrishnasamy, Sriramulu (International Journal of Pharmaceutical & Biological Archive, 2020)
Background: Industries development and population growth, migration of people from villages to cities, which release 1000 tons of municipal solid wastes (MSW) every day. India enormous quantities of disposable organic waste materials like MSW. MSW cannot be eaten directly by earthworms due to its bad odor, harmful insects, heat generates thermopile bacteria to organic wastes, etc. Hence, the organic wastes such as cattle waste – cow dung (CD) and agroindustrial waste-pressmud with clay soil high nutritive content were mixed in equal ratio and used as bedding material (BM). The experimental BMs were prepared on dry weight basis by mixing the MSW + BM in the following percentage: T1 – 20% BM + 80% MSW, T2 – 40% BM + 60% MSW, T3 – 60% BM + 40% MSW, and T4 – 80% BM + 20% MSW, and C1 control (BM alone) were also maintained separately. Results: The microbial enzyme activities such as cellulase, amylase, protease, and phosphatase were in the samples of (initial day), 15, 30, 45, and 60 days. The enzyme activity in the vermicompost has increased more than initial worm unworked compost. The maximum level of enzyme activity was observed in the vermicompost of T7 and it could be due to adequate moisture, higher fungal biomass, species-specific activity of earthworm (Eudrilus eugeniae) in terms of higher palatability, selective predation of microbes, and suitable environment, in the gut of E. eugeniae. Conclusion: The vermicompost obtained from T7 by E. eugeniae, on the basis of content of NPK, highest microbial population and enzyme activity was selected for the field application. The unutilized enormously available MSW can be vermicomposted along with any organic additives such as industrial Sludge’s, CD, sheep dung, pig manure, kitchen wastes (vegetable wastes), flower waste, and agricultural waste to convert into the valuable organic manure. In addition to this, it may be recommended that the vermicompost from MSW is utilized for sustainable organic agriculture.